2006
DOI: 10.1074/jbc.m605766200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Characterization of the EphB4·EphrinB2 Protein-Protein Interaction and Receptor Specificity

Abstract: Increasing evidence implicates the interaction of the EphB4 receptor with its preferred ligand, ephrinB2, in pathological forms of angiogenesis and in tumorigenesis. To identify the molecular determinants of the unique specificity of EphB4 for ephrinB2, we determined the crystal structure of the ligand binding domain of EphB4 in complex with the extracellular domain of ephrinB2. This structural analysis suggested that one amino acid, Leu-95, plays a particularly important role in defining the structural featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 35 publications
5
91
0
Order By: Relevance
“…In the past year the first structure of unclompexed A-class ligand (ephrin-A5) was reported [22], as well as the structures of ephrin-B1 [23] and, most importantly, that of a third ligand/ receptor complex -EphB4/ephrin-B2 [24]. These studies further illuminate the molecular determinants of the unique binding-partner specificities of Ephs and ephrins.…”
Section: Structures Studies Of the Eph/ephrin Interactionsmentioning
confidence: 78%
See 2 more Smart Citations
“…In the past year the first structure of unclompexed A-class ligand (ephrin-A5) was reported [22], as well as the structures of ephrin-B1 [23] and, most importantly, that of a third ligand/ receptor complex -EphB4/ephrin-B2 [24]. These studies further illuminate the molecular determinants of the unique binding-partner specificities of Ephs and ephrins.…”
Section: Structures Studies Of the Eph/ephrin Interactionsmentioning
confidence: 78%
“…Three interaction interfaces are indicated: dimerization and tetramerization -identified by crystallography [4] and confirmed by mutagenesis [25,26], as well as a potential oligomerization interface -identified by a random mutagenesis approach [26]. Schematic representation and a comparison of the interaction surfaces in the canonical intrasubclass EphB2/ephrin-B2 [20] and EphB4/ephrin-B2 [24] complexes with the unusual inter-subclass EphB2/ephrin-A5 complex [21*]. While ephrin-B2 has several interacting surface areas with the B-class receptors, the interaction of ephrin-A5 with EphB2 is mostly confined to the hydrophobic receptor surface channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the Ephephrin family of molecules is overexpressed across a variety of cancers, several molecules that target this signaling system are currently being investigated [56 -58]. Kinase inhibitors capable of interfering with the tumor promoting effects of Ephephrin signaling, peptides and antibodies capable of inhibiting Eph-ephrin interactions, and vaccines and immunotherapies capable of facilitating tumor lysis or rejection are some of the strategies that have been described to date [67][68][69][70][71][72]. Data on the safety and efficacy of these agents in lung cancer is very limited.…”
Section: Ephb3mentioning
confidence: 99%
“…EphA subclass receptors remarkably differ from EphB receptors because they lack a 4-residue insert in the H-I loop of the ligand-binding domain. Previously, the structures of the EphB2 and EphB4 ligand-binding domains have been determined in both the free state and in complex with ephrins or peptide antagonists (10,11,(12)(13)(14)(15). These studies have shown that the ligand-binding domains of EphB2 and EphB4 adopt the same jellyroll ␤-sandwich architecture composed of 11 antiparallel ␤-strands connected by loops of various lengths.…”
mentioning
confidence: 99%